Concerted integration of viral DNA termini by purified avian myeloblastosis virus integrase. - Fitzgerald, M L (J Virol, 1992)
Concerted integration of retroviral DNA termini, which produces a characteristic duplication of sequences at the integration site and formation of the proviral state, is a necessary step of the retroviral life cycle. We investigated the pairwise integration reaction catalyzed by purified avian retrovirus integrase by measuring the response to solution parameters and how the sequences of the viral termini, which comprise the avian imperfect inverted repeat, affect the reaction. When we optimized the reaction, an efficiency was achieved which approached that measured in systems using cytoplasmic extracts from virus-infected cells. The response of purified avian integrase to solution parameters was similar to that of the integration activity derived from cellular extracts. For strand transfer, the U3 viral terminal sequences were preferred to those of the U5 termini, a result we previously showed for the trimming reaction. That the sequence preference was the same for trimming and strand transfer may be further evidence that only one catalytic site is used for both reactions. A significant number of integration sites were sequenced. Interesting trends were found for the fidelity of the host duplications to the avian 6-bp duplication size, the clustering of the integration sites in the nonessential region of the lambda host DNA, and the sequence characteristics of the duplication sites.